High-Speed 3D Vision Based on Structured Light Methods - Leo Miyashita; Satoshi Tabata; Masatoshi Ishikawa (Metrology)
Three-dimensional measurement technologies based on computer vision have been developed with the aim of achieving perceptual speeds equivalent to humans (30 fps). However, in a highly mechanized society, there is no need for computers and robots to work slowly to match the speed of human perception. From this kind of circumstance, high-speed 3D vision with speeds far beyond that of humans, such as 1000 fps, has emerged. High-speed 3D measurement has great applicability not only for accurately recognizing a moving and deforming target but also for enabling real-time feedback, such as manipulation of the dynamic targets based on the measurement. In order to accelerate 3D vision and control the dynamic targets in real time, high-speed vision devices and high-speed image processing algorithms are essential. In this review, we revisit the basic strategy, triangulation as a suitable measurement principle for high-speed 3D vision, and introduce state-of-the-art 3D measurement methods based on high-speed vision devices and high-speed image processing utilizing structured light patterns. In addition, we introduce recent applications using high-speed 3D measurement and show that high-speed 3D measurement is one of the key technologies for real-time feedback in various fields such as robotics, mobility, security, interface, and XR.